Evaluation of serum zinc level and IL-18 mRNA expression in children with pneumonia - Yang, Shixiong; Shi, Jin (Cellular and Molecular Biology, 2021)
Pneumonia is currently one of the leading causes of death in children. Increased susceptibility to pneumonia may be due to their decreased immunity. One of the reasons for the decrease in immunity is zinc deficiency. In children with pneumonia, on the other hand, some cytokines are secreted, resulting in inflammation that spreads, persists, and makes treatment difficult for specialists. In this study, we investigated the serum zinc level in children with pneumonia and healthy children. Also, we tried to find its relationship with IL-18 mRNA expression as an inflammatory cytokine. For this purpose, serum zinc levels and IL-18 mRNA expression were evaluated in 120 children aged 3-60 months with pneumonia and 120 healthy children. After taking 2ml of blood from children and measuring serum zinc level, the level of the IL-18 mRNA was measured by real-time PCR. Total RNA was extracted by bioZOL™-G RNA Isolation Reagent kit. The primary cDNA was amplified by the extracted RNA, and in the next step, 2µl of cDNA were amplified by specific primers to measure IL-18 mRNA. The Beta-actin gene was also used as internal control and housekeeping gene. Results showed that the level of zinc in the patient group was 412.625±28.87?M and in the control group was 514.40±49.67?M. This difference was statistically significant (P=0.0053). Also, the expression of the IL-18 gene was increased in children with pneumonia, significantly (P=0.0015). Therefore, from the results, it can be deduced that children with zinc deficiency were at higher risk for a lung infection. Inflammatory cytokines such as IL-18 also were increased in these children. Hence, it can be concluded that zinc levels can reduce the expression of IL-18 mRNA and play an important role in the prevention and treatment of children with pneumonia.